GEPIKAS (MOVEMENT TO CARE FOR EDUCATION OF CHILDREN WITH DISABILITIES): EFFECTIVE EFFORTS TO EQUALIZE QUALITY AND INCLUSIVE EDUCATION FOR CHILDREN WITH DISABILITIES - Fachri Ferya (CV. RADJA PUBLIKA, 2024)
GEPIKAS is an initiative that aims to improve access to quality education for children with disabilities in Indonesia. In the context of inclusive education, GEPIKAS focuses on developing policies and programs that support the integration of children with disabilities into the formal education system. Through collaboration between the government, educational institutions, and the community, this movement seeks to create a friendly learning environment that supports the special needs of students. The importance of accurate data on the number and type of disabilities in educational institutions is one of the main pillars in the implementation of GEPIKAS. With applications such as the Student Learning Profile (PBS), it is hoped that inclusive student data collection can be carried out in detail, so that the policies taken can be more targeted. In addition, training for educators on how to teach children with disabilities is also a main focus to ensure the quality of education received. Through socialization and training activities, GEPIKAS not only seeks to increase public awareness of the importance of inclusive education, but also encourages active participation from various parties in supporting children with disabilities. Thus, GEPIKAS is expected to become an effective model in equalizing quality education in Indonesia, ensuring that every child, without exception, gets their right to learn and develop.